Fracking: A creature of government?. Issue 8 (December 2016) - Counts, Gage; Block, Walter E
Like most other things, fracking has its good and bad points. In the former regard, it is a technological breakthrough that can increase the supplies of energy of the entire economy. In the latter, it has been linked with an increased incidence of earthquakes and water pollution, surely negatives. As well, there is some evidence fracking would not exist, at least not to the present extent, were it not for government subsidies, which, we argue, misallocate resources.